Green tourist behavior analysis and its relationship with the choice of eco-tourism destination: An empirical study - José Manuel Vicente (International Journal of Geoheritage and Parks)
Travelers may now actively support environmental protection while having a great time on their trips thanks to the growing trend of eco-tourism. This study aims to examine, while accounting for pro-environmental behavior, the effects of digital green marketing and visitors' environmental attitudes on their willingness to return to eco-destinations. In addition, the hypothesis was investigated in this work using the structural equation model (SEM). The study's findings suggest that visitors' attitudes about the environment and digital green marketing have a positive influence on their environmental behavior. Moreover, it has been found that tourists' intentions to return are positively impacted by their ecologically conscious conduct. Studies have indicated that travelers' intentions to return to eco-destinations are significantly influenced by their pro-environmental conduct. By examining the relationship between digital green marketing initiatives, travelers' pro-environmental views and actions, tourism ecosystems, and their intention to return to eco-destinations, this study will add to the body of current work. Additionally, the study's findings will provide clear guidance to destination marketing organizations (DMOs) on how to effectively market their eco-destinations, which will motivate travelers to follow responsible travel guidelines and encourage return trips to these eco-friendly locations.